Service-Oriented Computing - ICSOC 2012 Workshops ICSOC 2012, International Workshops ASC, DISA, PAASC, SCEB, SeMaPS, WESOA, and Satellite Events, Shanghai, China, November 12-15, 2012, Revised Selected Papers - Ghose, Aditya.; Zhu, Huibiao.; Yu, Qi.; Delis, Alex.; Sheng, Quang Z.; Perrin, Olivier.; Wang, Jianmin.; Wang, Yan. (Lecture Notes in Computer Science,, 2013)
This book constitutes the thoroughly refereed proceedings of the 2012 ICSOC Workshops consisting of 6 scientific satellite events, organized in 3 main tracks including workshop track (ASC, DISA. PAASC, SCEB, SeMaPS and WESOA 2012), PhD symposium track, demonstration track; held in conjunction with the 10th International Conference on Service-Oriented Computing (ICSOC), in Shanghai, China, November 2012. The 53 revised papers presents a wide range of topics that fall into the general area of service computing such as business process management, distributed systems, computer networks, wireless and mobile computing, grid computing, networking, service science, management science, and software engineering.